Assessment of Green Infrastructure for Conservation Planning using Cadastral Data in Seoul, South Korea - Gon Park (Environmental Science and Sustainable Development, 2018)
Green infrastructure has been used for environmental conservation and management with many similar concepts such as green-space network, green-link network, and green-ways network based on the objectives of the cities for greening. Seoul established the 2030 Seoul City Master Plan that contains green-link network projects to connect critical green areas within the city. However, the plan does not have detailed analysis for the green infrastructure to incorporate land-cover information to many structural classes. This study maps green infrastructure networks of Seoul for complementing their green plans with identifying and ranking green areas. Hubs and links that are the main elements of green infrastructure have been identified through incorporating cadastral data of 967,502 parcels to 135 of land use maps using Geographic Information System. The study extracted 1,365 of green areas that represent an area of 24,530 ha within the city and buffered these areas to identify districts as critical green areas that have hubs and links. At a city scale, the study used 103,553 of parcel data for ranking extracted 20 districts, and 17,860 of parcel data for ranking extracted 42 links connecting the districts. At a district scale, this study used 87,826 of parcel data for analyzing the status of potential links within the districts and ranking these districts for green infrastructure. This assessment analyzes the main elements of green infrastructure and suggests site prioritization for green infrastructure under variable scenarios of green and developed areas in a metropolitan city.